SYURA DAN DEMOKRASI DALAM PERSPEKTIF AL-QUR'AN (TELAAH QS. ASY-SYURA: 38 DAN AL-IMRAN: 159) - Akhmad Roja Badrus Zaman (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
Nowaday, the f stereotypical views of Islam with radicalism is increasing and also revives the wave of Islamophobia, both in terms of religion, culture, and politics. In the context of the Indonesian state, for example, Pancasila democracy is being sued by several groups who wish to make religious laws as state constitutions to reap the pros and cons among the public. They assume that the Indonesian state system is â€œevilâ€ because it is not in accordance with the instructions in the Qurâ€™an. This article the author tries to position democracy in the perspective of the Qurâ€™an. From the research carried out it can be seen that indeed in Lafdziyah, democracy has never been explicitly mentioned in the Qurâ€™an. The Qurâ€™an only mentions orders to consult (syura). In this case, Shura is narrower than democracy. Especially if you examine the opinions of some intellectuals who claim that the harmony of shura and democracy lies in several principles of democracy, namely justice (al-â€™adalah), equality (al-musawah), independence (al- hurriyyah), deliberation (ash-shura), and accountability (al-masâ€™uliyyah). From these principles it can be seen that shura is only a small part of a broader democratic system. However, democracy does not conflict with the Qurâ€™an at all. Al-Quran actually provides a moral foundation in building a democratic system